The Causes of Disputes of Final Accounts: Malaysian Case Law Analysis - Kong, Sio Kah; Yeow, Win Shyang (2016)
The closing of final account has frequently caused disputes and ended up with court cases in construction industry. The prolongation of closing final account due to disputes is devastating to contracting parties especially contractors. Therefore, it is crucial to identify the significant causes of disputes of final accounts. Such disputes can be due to the contractor, consultant, employer or uncertain contract clauses. The purpose of this study is to identify the most significant causes of disputes for final accounts from Malaysian law cases. These causes are categorised according to the types of causes which are contractor-related, consultant-related, employer-related and contract-related. Case law analysis is being adopted for primary data analysis for this study. The findings of this study discovered that the most significant cause of disputes of final accounts is the unreasonable late payments and non-payments by employers. The next significant cause of the disputes is the inadequate contract administration by contractors which is mainly due to error in submitting final claims. This is followed by the inadequate contract administration by the consultants where the consultants or third parties delayed in certifying the final accounts. Contract related causes are relatively less significant which are mainly related to conclusiveness of final account due to subsequent defective works and back to back clauses. Inexperienced contractor which led to poor quality of work is found to be the least significant cause of disputes for final accounts. Upon the identification of the significant causes of disputes for final account in Malaysia, awareness of avoiding disputes for final account can be created among contract parties and possible solutions can be obtained for Malaysian construction industry.